Migration to IBM CICS Transaction Server for z/VSE - Wacker, Klaus; Salm, Ingolf (IBM Corporation, International Technical Support Organization, 2017)
Abstract The IBM® CICS® Transaction Server for z/VSE® (CICS TS for z/VSE) 2.1 provides functions to improve application programming, system programming, system management, and data security and availability. With CICS TS for z/VSE 2.1, you can use the extended functionality of Basic Security Manager. CICS TS for z/VSE 2.1 can be administrated by the IBM CICS Explorer® function on a workstation, which allows CICS management in a convenient way. This IBM Redbooks® publication provides information to help you install, tailor, and configure the CICS TS for z/VSE 2.1 product. The book is intended for IBM z/VSE customers and IBM technical personnel who are responsible for planning and migrating to IBM z/VSE 6.1 and CICS TS for z/VSE 2.1. The book also provides information to help you understand the affect of migrating to CICS TS for z/VSE 2.1. It provides detailed guidance and samples for installing and configuring CICS TS for z/VSE 2.1. Also included in the book is a description of the CICS TS for z/VSE 2.1 features and capabilities and the affect of removing obsolete functions. The book also covers security and performance issues and provides samples for first level problem determination through the use of memory dumps or the use of trace tools.
Number on resource description page: SG24839000. - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed July 10, 2017)
Keywords: Information technology -- Management; Computer networks -- Management; Client/server computing; CICS (Computer system); Technologie de l'information; Gestion; Réseaux d'ordinateurs; Gestion; Architecture client-serveur (Informatique); CICS (Système informatique); Computer networks; Management; Information technology; Management